2011
DOI: 10.1111/j.1365-2672.2011.05121.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of Candida albicans isolates from patients and health care workers in a neonatal intensive care unit

Abstract: Aims:  The aim of this study was to investigate the genetic relatedness between Candida albicans isolates and to assess their nosocomial origin and the likeliness of cross‐transmission between health care workers (HCWs) and hospitalized neonates in a neonatal intensive care unit (NICU). Methods:  We retrospectively analysed 82 isolates obtained from 40 neonates and seven isolates from onychomycosis of the fingers of five HCWs in a Tunisian NICU by using pulsed‐field gel electrophoresis (PFGE) and randomly ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
0
20
1
1
Order By: Relevance
“…To determine whether strain RR CL evolved from S CL or replaced S CL under selection pressure of CAS, RAPD genotyping of the clinical isolates was performed. The efficacy of RAPD as a typing method for clinical C. albicans isolates was previously demonstrated (17,18). RAPD revealed a clonal relationship between the isolates (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…To determine whether strain RR CL evolved from S CL or replaced S CL under selection pressure of CAS, RAPD genotyping of the clinical isolates was performed. The efficacy of RAPD as a typing method for clinical C. albicans isolates was previously demonstrated (17,18). RAPD revealed a clonal relationship between the isolates (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…The strengths of MLST are not only a highly discriminative tool in analyzing the genetic relatedness among sequential isolates from the same or different study sites, but also allowing the inter-laboratory comparison worldwide. However, MLST may have some limitations in typing isolates from different patients, since some studies had shown different PFGE or fingerprinting patterns in shared DST isolates [19,41,42]..Although MLST has been proven superior to PFGE and at least comparable to Southern hybridization [43,44], a strict definition of a nosocomial cluster as those occurring within a period of 90 days [18] would make the cluster identification more effective and reliable.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to MLST, the methods include polymerase chain reaction M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 15 fingerprinting and random amplification of polymorphic DNA [39], restriction fragment length polymorphism analysis [40], pulsed-field gel electrophoresis (PFGE) [19], and Southern blot hybridization with discriminating probes [38]. The strengths of MLST are not only a highly discriminative tool in analyzing the genetic relatedness among sequential isolates from the same or different study sites, but also allowing the inter-laboratory comparison worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations